Investigation of the Models of Flow through Fractured Rock Masses Based on Borehole Data - Long Tan; Wei Xiang; Jin Luo; Qingbing Liu; Xu Zuo (Advances in Civil Engineering)
When only limited borehole data are available, making optimum use of the existing data is crucial for performing a preliminary assessment of the investigated site. In this paper, the relationships between the borehole data and the permeability coefficient were first analyzed. These relationships were then used to establish a model for estimating the permeability coefficient of rock mass that takes into account the influence from the confining pressure on the seepage flow. The proposed model can reduce the number of hydraulic tests which are time consuming and very costly and allow the determination of change in the permeability coefficient throughout the borehole. The flow model could assist in providing important references for selecting an appropriate permeability coefficient in hydrogeological simulation and in evaluating the condition of large cracks developed in boreholes. In general, the seepage flow model developed in this study will contribute to the design practice of a tunnel project constructed in fractured rock masses.